Hypoglycemic Effect of Lycopersicon esculentum (Tomato) on Alloxan-Induced Diabetic Rats (Journal of Biochemistry, Microbiology and Biotechnology, 2021)
Diabetes mellitus has been a key degenerative disease affecting the world’s population. Lycopersicon esculentum (Tomato), a fruit consumed by many and known to have certain phytochemicals was used to determine its hypoglycemic effect on alloxan induced diabetic rats. The tomato was dried, pulverized and dissolved in distilled water and administered orally to albino rats in various concentrations according to their body weight. 30 albino rats were divided into 6 groups of 5 rats each. Groups I and II served as normal and diabetic control respectively, while groups III to VI were induced with diabetes and treated with different concentrations of the prepared tomato. After 14 days of treatment with various concentrations of tomato, there was a marked decrease in blood sugar levels at all the study concentrations. The result of the lipid profile a significant increase (p
Keywords: Hypoglycemic; Lycopersicon esculentum; Tomato; Alloxan-Induced Diabetic Rats; LDL- and HDL cholesterol